Portfolio inertia under ambiguity - Takao Asano (Osaka University, Institute of Social and Economic Research (ISER), 2004)
We consider individual's portfolio selection problems. Introducing the concept of ambiguity, we show the existence of portfolio inertia under the assumptions that decision maker's beliefs are captured by an inner measure, and that her preferences are represented by the Choquet integral with respect to the inner measure. Under the concept of ambiguity, it is considered that a o-algebra is not necessarily an appropriate collection of events to which a decision maker assigns probabilities. Furthermore, we study the difference between ambiguity and uncertainty by considering investors' behavior.
Keywords: D81; G11; 330; Ambiguity; Knightian Uncertainty; Portfolio Inertia; Portfolio-Management; Anlageverhalten; Theorie; Entscheidung bei Unsicherheit